(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Phellodendron amurense was used as natural dye source. Orthogonal experiment was carried out to select optimal extract process of phellodendron amurense dye. The orthogonal analysis results showed extract temperature was the most important factor. Stability investigation showed phellodendron amurense extract was stable to weak acid and alkaloid environment. Common metal ion had little effects on absorbance of phellodendron amurense extraction. Wool fabric and silk fabric had been dyed with phellodendron amurense aqueous solution. Solarization experiment showed high concentration dyeing sped up photofading rate and the dyed silk fabric was more sensible to the solarization. Vitamin C acid treatment slowed down photofading rate.